Mid- to long-term results of total lumbar disc replacement: a prospective analysis with 5- to 10-year follow-up - Siepe, Christoph; Heider, Franziska; Wiechert, Karsten; Hitzl, Wolfgang; Ishak, Basem; Mayer, Michael H. (The spine journal, 2014)
Background context - The role of fusion of lumbar motion segments for the treatment of intractable low back pain (LBP) from degenerative disc disease (DDD) without deformities or instabilities remains controversially debated. Total lumbar disc replacement (TDR) has been used as an alternative in a highly selected patient cohort. However, the amount of long-term follow-up (FU) data on TDR is limited. In the United States, insurers have refused to reimburse surgeons for TDRs for fear of delayed complications, revisions, and unknown secondary costs, leading to a drastic decline in TDR numbers. - Purpose - To assess the mid- and long-term clinical efficacy as well as patient safety of TDR in terms of perioperative complication and reoperation rates. - Study design/setting - Prospective, single-center clinical investigation of TDR with ProDisc II (Synthes, Paoli, PA, USA) for the treatment of LBP from lumbar DDD that has proven unresponsive to conservative therapy. - Patient sample - Patients with a minimum of 5-year FU after TDR, performed for the treatment of intractable and predominant (≥80%) axial LBP resulting from DDD without any deformities or instabilities. - Outcome measures - Visual analog scale (VAS), Oswestry Disability Index (ODI), and patient satisfaction rates (three-scale outcome rating); complication and reoperation rates as well as elapsed time until revision surgery; patient's professional activity/employment status. - Methods - Clinical outcome scores were acquired within the framework of an ongoing prospective clinical trial. Patients were examined preoperatively, 3, 6, and 12 months postoperatively, annually from then onward. The data acquisition was performed by members of the clinic's spine unit including medical staff, research assistants, and research nurses who were not involved in the process of pre- or postoperative decision-making. - Results - The initial cohort consisted of 201 patients; 181 patients were available for final FU, resembling a 90.0% FU rate after a mean FU of 7.4 years (range 5.0-10.8 years). The overall results revealed a highly significant improvement from baseline VAS and ODI levels at all postoperative FU stages (p<.0001). VAS scores demonstrated a slight (from VAS 2.6 to 3.3) but statistically significant deterioration from 48 months onward (p<.05). Patient satisfaction rates remained stable throughout the entire postoperative course, with 63.6% of patients reporting a highly satisfactory or a satisfactory (22.7%) outcome, whereas 13.7% of patients were not satisfied. The overall complication rate was 14.4% (N=26/181). The incidence of revision surgeries for general and/or device-related complications was 7.2% (N=13/181). Two-level TDRs demonstrated a significant improvement of VAS and ODI scores in comparison to baseline levels (p<.05). Nevertheless, the results were significantly inferior in comparison to one-level cases and were associated with higher complication (11.9% vs. 27.6%; p=.03) and inferior satisfaction rates (p<.003). - Conclusions - Despite the fact that the current data comprises the early experiences and learning curve associated with a new surgical technique, the results demonstrate satisfactory and maintained mid- to long-term clinical results after a mean FU of 7.4 years. Patient safety was proven with acceptable complication and reoperation rates. Fear of excessive late complications or reoperations following the primary TDR procedure cannot be substantiated with the present data. In carefully selected cases, TDR can be considered a viable treatment alternative to lumbar fusion for which spine communities around the world seem to have accepted mediocre clinical results as well as obvious and significant drawbacks.
Gesehen am 31.08.2020